2020
DOI: 10.3390/plants9121773
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobacteria and Arbuscular Mycorrhizal Fungi of Oil Crops (Physic Nut and Sacha Inchi): A Cultivable-Based Assessment for Abundance, Diversity, and Plant Growth-Promoting Potentials

Abstract: Nowadays, oil crops are very attractive both for human consumption and biodiesel production; however, little is known about their commensal rhizosphere microbes. In this study, rhizosphere samples were collected from physic nut and sacha inchi plants grown in several areas of Thailand. Rhizobacteria, cultivable in nitrogen-free media, and arbuscular mycorrhizal (AM) fungi were isolated and examined for abundance, diversity, and plant growth-promoting activities (indole-3-acetic acid (IAA) and siderophore produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…So far, few secondary metabolites from gut microbes have been well characterized. First, the majority of bacteria from nature are currently unculturable with traditional laboratory techniques [ 58 ]. Second, the expression of bioactive secondary metabolites may remain silent or at a relatively low level [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, few secondary metabolites from gut microbes have been well characterized. First, the majority of bacteria from nature are currently unculturable with traditional laboratory techniques [ 58 ]. Second, the expression of bioactive secondary metabolites may remain silent or at a relatively low level [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial colony presented on the agar medium was collected and sub-cultured on the same medium until becoming an axenic culture. The capability to fix atmospheric nitrogen of isolate CGC-5 was estimated following a modified acetylene reduction assay addressed by Wiriya et al [ 26 ], and its nitrogenase activity was 10.57 ± 0.26 nmol h −1 per mg cell protein. The isolate was preserved in 20% ( v / v ) glycerol at −20 °C before further investigation.…”
Section: Methodsmentioning
confidence: 99%
“…The auxin family consists of diverse molecular members such as IAA (the most abundant and basic auxin), indole-3-butyric acid, indole-3-propionic acid, etc. The capability to form auxins was estimated using a modified Salkowski’s colorimetric method, described in Wiriya et al [ 26 ]. Briefly, rhizobacteria were grown in 5 mL liquid media (Burk’s broth for isolate CGC-5 and ISP2 broth for isolate TCM1-050).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, few studies have been done on the interaction of these fungi with Plukenetia volubilis species and their diversity. Previous studies under controlled conditions (greenhouse) have shown that AM fungi (genera: Paraglomus , Glomus , Acaulospora , Claroideoglomus , and Funneliformis ) stimulate growth and development and improve the drought tolerance of sacha inchi seedlings through alterations in the morphological, physiological, and biochemical characteristics of the roots [ 27 , 28 ]. Likewise, some AM fungal species have been reported in sacha inchi rhizospheric soils in the Peruvian rainforest and in Thailand [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%